TRANSFORMASI KURIKULUM PAI DI INDONESIA: DARI KOLONIALISME HINGGA KURIKULUM MERDEKA - Wahyuni, Amalia Desy; Bunai, Bunai (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The development of the Islamic Religious Education (PAI) curriculum in Indonesia is deeply rooted in the nation’s historical, ideological, and socio-educational dynamics. Over time, the PAI curriculum has shifted from a normative-doctrinal model to a more applicative, contextual, and adaptive framework in response to global challenges such as globalization, radicalism, and digitalization. This study addresses two main questions: how has the historical trajectory of the PAI curriculum evolved, and what are its current challenges and future directions? Employing a descriptive qualitative method through library research, this study analyzes historical documents, educational policies, and academic literature. The findings reveal significant curriculum transformations, yet also persistent gaps in implementation, including the dominance of lecture-based teaching, disparities in educational resources, and limited integration of religious moderation and digital literacy. Therefore, this study emphasizes the need to reconstruct the PAI curriculum to integrate Islamic values with 21st-century competencies, enhance teacher capacity, and allow school-level autonomy for more contextual and inclusive religious education.